Pengaruh Manual Lymph Drainage Vodder (MLDV) Terhadap Lymphedema Lengan Pasca Operasi Carcinoma Mammae Di Rumah Sakit X Surabaya - ignatius heri dwianto; Arief Widya Prasetya (Jurnal Keperawatan Muhammadiyah, 2023)
Objective: Â Breast cancer in adult women as much as 16% causes death. The mastectomy method is the most widely used because it has the highest cure rate. The results of the study found that of 360 patients undergoing breast cancer therapy, 42% were found to have lymphedema in their arms. Lymphedema is the accumulation of high-protein fluid in the interstitium due to failure of lymphatic transport or dysfunction of interstitial protein processing. Manual Lymphatic Drainage (MLD) is one of the modalities to reduce edema in the arms after mastectomy or postoperative Ca. MLDV (Manual Lymphatic Drainage Vodder) is a gentle yet very specific type of massage designed to improve lymph drainage, remove excess fluid from tissues, reduce inflammation and relieve symptoms such as pain and this method is an extension of MLD.Methods: The study design used a Quasi experimental pretest and posttest one group design with subjects taken from secondary data of 30 medical record data, then divided into the pretest group (measurement of arm segment volume before MLDV intervention) and the posttest group (measurement of arm segment volume after MLDV was performed). each session is 45 minutes, a week 2-3 times up to 10 sessions). Furthermore, data was collected and analyzed statisticallyResults: The results of the data normality test on the volume of the pre MLDV segment and the volume of the post MLDV segment all show a value of p> 0.05, so the data is normally distributed. The results of the paired t-test showed the volume of the pre MLDV segment and the volume of the post MLDV segment with a significance value of 0.040. Because both showed a p value <0.05, there was a significant difference before and after the MLDV interventionConclusion: Manual Lymphatic Drainage Vodder (MLDV) each session is 45 minutes, 2-3 times a week for up to 10 sessions can reduce edema in the arms after mastectomy or post-Ca mammae surgery.